Patient's Coping of Anxiety Level of Dialysis Patients - Kristia Lulu Sabrina; Mori Agustina br Perangin-Angin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of coping with anxiety levels. The research method used is descriptive correlative using Cross-Sectional. The results showed moderate anxiety levels in the hemodialysis installation at Advent Bandung Hospital with 86 people (96.63%). In conclusion, coping mechanisms influence the patient's anxiety levels. Keywords: Anxiety, Dialysis, Patient Coping